Providing specimen transport through an online marketplace in the Northern region of Ghana - Abass Abdul-Karim; David Opare; Ulysses Balis; Lee F. Schroeder (AOSIS, 2023)
Background: Integrated diagnostic networks, which are themselves dependent on robust specimen transport solutions, are fundamental to effective healthcare systems. Objective: This study aimed to pilot an online marketplace for the transport of specimens throughout a laboratory network in Ghana. Methods: Independent drivers were matched with health facilities that required specimen transport using a suite of mobile applications and web portals developed for this study. This marketplace was piloted with seven drivers, two laboratories, and five health facilities in Ghana's Northern region from March 2019 to October 2019. Results: During the pilot, 182 deliveries were completed for 691 patients, including 4118 laboratory tests for antenatal care, disease surveillance, and clinical testing. Testing included 34 tests for communicable and non-communicable diseases. All but two specimens (laboratory cancellations) were successfully delivered and tested. The median time from request to encrypted emailing of results was 19.7 h, while that for a drop-off request was 0.9 h. In the midwife registry, the median time from patient visit to result recording was 1 day, compared to 4 days in the same months in 2018, and the number of mothers without documented testing decreased from 41 to 3. Similarly, the proportion of tuberculosis specimen deliveries from Buipe Polyclinic to Tamale Zonal Laboratory taking over 1 day fell from 62% at baseline to 3% during the pilot. Conclusion: An online marketplace successfully orchestrated the delivery of laboratory specimens under a variety of clinical circumstances, reducing overall turn-around time without diminution of the overall specimen delivery process. What this study adds: This study established the efficacy of an online marketplace to orchestrate timely and high-quality delivery of specimens within a laboratory network.